Burnout and Adherence to Pressure Injury Prevention Guidelines Among ICU Nurses in a Teaching Referral Hospital - Chiyar Edison Sunarya (Nursing Current: Jurnal Keperawatan, 2026)
Burnout is a major problem among intensive care nurses, yet its relationship with pressure injury prevention adherence has not been examined within the Indonesian context. This study aimed to determine the association between burnout levels and adherence to pressure injury prevention guidelines among nurses working in intensive care units of a type-A teaching hospital. A cross-sectional study was conducted among 144 ICU nurses in a teaching referral hospital in Depok. Data were collected using the Questionnaire for Adherence to Recommendations for Pressure Ulcer Prevention (QARPPU) and the Maslach Burnout Inventory–Human Services Survey (MBI-HSS). Univariate analyses summarized respondent characteristics, and chi-square tests with Cramer’s V examined the association between burnout and adherence.It is revealed that most nurses showed adequate adherence to pressure injury prevention practices (58.3%). High burnout was evident in 45.8% of respondents. There was a strong statistical association between burnout level and the adherence of prevention of pressure ulcers (χ² = 27.65, p < 0.001), with a moderate effect size (Cramer’s V = 0.438). Burnout was significantly associated with adherence to pressure injury prevention guidelines among intensive care nurses. Although high burnout prevalence was comparatively lower, this is still an important issue to be solved by hospital management.